2003
DOI: 10.1046/j.1525-1446.2003.20506.x
|View full text |Cite
|
Sign up to set email alerts
|

Using Roy's Adaptation Model When Caring for a Group of Young Women Contemplating Quitting Smoking

Abstract: This article provides an overview of the use of Roy's adaptation model when caring for a group of young women who were in the precontemplation phase of smoking cessation. The model served as a guide to assess each member's level of adaptation in each of the four modes to identify actual or potential adaptation problems and then examining the stimuli that influence those problems. Nursing interventions focused on approaches to the management of stimuli to promote adaptation for the group by helping the members … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…However, study results reveal that severity of illness and adjuvant cancer treatment had the strongest association with bio-psycho-social responses and should be considered the focal environmental stimuli in determining adaptation (Samarel et al 1998, Nuamah et al 1999. Villareal (2003) found that, in caring for a small group of female smokers, the RAM can be used as a guide to provide comprehensive nursing care.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…However, study results reveal that severity of illness and adjuvant cancer treatment had the strongest association with bio-psycho-social responses and should be considered the focal environmental stimuli in determining adaptation (Samarel et al 1998, Nuamah et al 1999. Villareal (2003) found that, in caring for a small group of female smokers, the RAM can be used as a guide to provide comprehensive nursing care.…”
Section: Introductionmentioning
confidence: 94%
“…The RAM is one of the most fully developed and widely used of all nursing conceptual models (Riehl & Roy 1980, Veliog lu 1999. Nurses act to promote patients' levels of adaptation during health and illness using the nursing process (Dixon 1999, Villareal 2003, Patton 2004. Environmental stimuli include focal, contextual and residual stimuli (Samarel et al 1998, Willoughby et al 2000 Roy Figure 1 Conceptual-theoretical-empirical structure of adaptation to heart failure.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…In a training programme designed to prevent amputation in people with diabetes, Scollan‐Koliopoulos () compared RAM and the Health Belief Model and found that RAM was a better instrument for designing a community‐based plan. Villareal () found that in caring for a small group of female smokers, RAM can be used as a guide to provide comprehensive nursing care.…”
Section: Introductionmentioning
confidence: 99%
“…Public health cancer intervention research conducted by nurses has often focused on the individual‐level, typically attempting to influence modifiable behaviors (Abbott, ) or diminish direct exposure to carcinogens (Larsson, ; Villareal, ); similarly, precision medicine focuses on intervening at a micro‐individual, genomic level. Little public health nursing research has focused on built and social environment stress exposures that influence genomes and their resulting effects on cancer.…”
mentioning
confidence: 99%